A randomized controlled trial comparing tacrolimus versus hydrocortisone for the treatment of atopic dermatitis in children: new perspectives on interferon gamma-induced protein and growth-related oncogene-α - Binsaleh, Ammena Y.; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Elberri, Eman I.; Kotkata, Fedaa A.; El-Khateeb, Eman; Kamal, Marwa; El-samongy, Marwa Ahmed; Hamouda, Amir O.; Alghamdi, Amira M.; Alrubia, Sarah; Salahuddin, Muhammed M.; et al. (Frontiers in Medicine, 2024)
Introduction Atopic dermatitis (AD) is a type of chronic inflammatory disorder that affects children. Aim To investigate whether hydrocortisone or tacrolimus could be more effective for treating AD in children. Patients and methods This clinical randomized investigation included 100 children with AD who met the eligibility criteria. AD patients were recruited from Tanta University’s Dermatology Department and divided into two groups (n = 50)., For four months, group 1 (the hydrocortisone group) received topical hydrocortisone cream. Group 2 received topical tacrolimus for four months. A dermatologist evaluated the patients at the start and four months after the treatment had been initiated to measure serum concentrations of neutrophil chemoattractant growth-related oncogene-α (GRO-α), interferon gamma induced protein 10 (IP-10), tumor necrosis factor alpha (TNF-α), vascular adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1). All patients were examined using the modified Eczema Area and Severity Index (mEASI) score. Results Tacrolimus group showed a significant reduction in serum levels of all measured biomarkers (p < 0.05) when compared to its baseline and when compared to the hydrocortisone group. Both groups displayed a significant decline in mEASI score in comparison with their baseline values (p < 0.05). Conclusion In children with AD, tacrolimus reduces inflammatory biomarkers better than hydrocortisone, suggesting its potential as a more effective treatment option. Clinical trial registration https://clinicaltrials.gov, identifier NCT05607901.